Performance Tasks as a Strategy to Enhance Learning Motivation among Kindergarten Group B Children - Devi Ferdiani; Rr Agustien Lilawati; Mush'ab Al Umairi (Al-Qalam Institue, 2025)
This study aims to examine the improvement of children’s learning motivation through the implementation of performance task activities in Group B at TK Bunga Bangsa. Using a descriptive qualitative approach, the research involved 22 children (11 boys and 11 girls). Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that prior to the intervention, children’s learning motivation was relatively low, with only 9 children (40.9%) demonstrating consistent focus and enthusiasm. After the implementation of various performance tasks—such as reciting short prayers, role-playing with zoo themes, explaining the chicken life cycle, and presenting artwork using banana midrib stamping techniques—children’s motivation increased significantly. A total of 17 children (77.3%) showed higher levels of focus, confidence, and active participation. These results suggest that performance task activities provide meaningful and enjoyable learning experiences that effectively enhance early childhood learning motivation. The study implies that performance tasks can serve as an alternative pedagogical strategy to support more engaging and successful early childhood education.